(untitled) (Research, Society and Development, 2021)
Objective: To analyze the kinetics of creatine kinase (CK) and its concentrations in resistance training in circuit, with different volumes of a fixed weight of twenty maximum repetitions (20RM), for trained (TR) and untrained (DT) men. Method: The sample comprised, by volunteering, 18 men (9 volunteers TR and 9 DT), aged between 18 and 35 years. After receiving information about the project, the volunteers, carry out a physical evaluation, and later tests and retests of a maximum repetition (1RM) and 20RM. The training protocol consisted of: 3 exercise sessions (leg press, bench press, flexing table, front puller), with intervals of 1 minute between exercises and 2 minutes between each lap, totaling 3 laps per session. Each session had different volumes (12, 16 and 20 repetitions) and a 96-hour (h) interval between sessions. The measurement of CK, from a blood sample, was done at rest, 24, 48 and 72h after the session. The data were hanged by the STATISTIC 7 software, adopting a significance of p<0.05. Results: The groups dissipated from CK after 48h at rest, with no difference between groups, however, there were greater adjustments of CK/repetitions in the previous combinations of the concentric failure, which in DT occurred in the session of 16 repetitions (1.46±0.50), no longer TR occurred in the 20 repetition session (1.71±0.62). Conclusion: The CK concentrations were not influenced by the training level of the owners, but by the proximity to a concentric failure, where the peak of 48h was relevant to the training prescription.